Reforming EU fiscal governance: A golden rule for public investments? - Sebastian Blesse; Florian Dorn; Max Lay (EconPol Forum, 2023)
The need for larger public investment in Europe drew attention to its role in the EU fiscal governance. The current reform proposal of the European Commission aims to incentivize higher public investment by softening deficit rules, likely at the cost of incurring higher deficits. If fiscal rules are too rigid, they can deter public investment. Flexible rules can increase public investment, but depending on how they are designed, this can lead to higher levels of public debt. We propose a modified golden rule that enhances public investment while maintaining fiscal sustainability: debt-financed spending should be limited to net investment, while debt-financed investment is capped by a deficit rule. Other primary expenditures (excluding net investment) need to be balanced. Investment categories relevant to the golden rule must be narrowly and clearly defined to avoid creative accounting tricks. The narrow definition of investments should be limited to investment spending that produces new capital stock and may stimulate sustainable economic growth.
Keywords: 330